Харьцаа заасан нэгж өгүүлбэрийн гишүүдийг хураах хэрэглүүр болгох нь: Англи Монгол хэлний жишээн дээр - Ц.Отгонсүрэн (Acta Mongolica, 2014)
In this article, we are using the term «RELATIVE ELEMENT» instead of the PREPOSITION in English and the POSTPOSITION in Mongolian, as their cross-linguistic meaning depending on their different positions and structures (described as a single word in English and as a morpheme in Mongolian) in both languages. Of their some alternative functions, the most common one is to indicate the relations between separate words or members in a sentence. The above mentioned relation is said to be «NOUN +NOUN» or «NOUN+VERB». Based on the second, there is another function that is to truncate members in clause which we are stressing, here, in the article. It is appeared in the syntactic relation, that is to say, in the deep structure in the languages. Like being able to reveal any relative elements in a sentence, it is possible to find out any full sentences or clauses (relative clause, adverbial clause, object clause and answer of WH-questions etc.) through the relative elements.